Competition's Moment: The Jitney-Bus and Corporate Capitalism in the Canadian City, 1914-29 - Davis, Donald (Urban History Review / Revue d'histoire urbaine, 1989)
Using a social constructivist approach to the history of technology, this article examines the jitney-bus phenomenon in urban Canada between 1914 and 1929. These hailed-ride common carriers briefly flourished during the First World War, but were soon suppressed by municipal regulators. Their suppression, though intended to protect public transit from "destructive" competition, in fact weakened it by depriving it of a flexible, speedy alternative to the private automobile. The article explains both the importance of jitneys in a modern context and the reasons for—and the social groups behind—their quick demise in most Canadian cities during the First World War.